2015
DOI: 10.4236/ojmm.2015.51001
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Formation on Resorbing Magnesium Implants

Abstract: Background: Implant-associated infections are a result of bacterial adhesion to an implant surface and subsequent biofilm formation at the implantation site. This study compares different magnesium materials based on their ability to resist bacterial adhesion as well as further biofilm formation. Material and Methods: The surfaces of four magnesium-based materials (Mg2Ag, Mg10Gd, WE43 and 99.99% pure Mg) were characterized using atomic force microscope. In addition, the samples were tested for their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
2
12
0
2
Order By: Relevance
“…In addition, these could be neutralized by wound liquid or by the blood flow to create a moderately alkaline niche where bacteria could thrive while being protected from the host immune cell attack. In agreement with this notion, in a recent in vitro study bacterial biofilms were developing on serum and phosphate buffer treated magnesium alloy surfaces . Based on these observations, it is conceivable that a corroding magnesium‐organic environment interface could provide a niche where bacteria could initially settle and thrive as a first step toward biofilm formation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, these could be neutralized by wound liquid or by the blood flow to create a moderately alkaline niche where bacteria could thrive while being protected from the host immune cell attack. In agreement with this notion, in a recent in vitro study bacterial biofilms were developing on serum and phosphate buffer treated magnesium alloy surfaces . Based on these observations, it is conceivable that a corroding magnesium‐organic environment interface could provide a niche where bacteria could initially settle and thrive as a first step toward biofilm formation.…”
Section: Discussionmentioning
confidence: 64%
“…In agreement with this notion, in a recent in vitro study bacterial biofilms were developing on serum and phosphate buffer treated magnesium alloy surfaces. 65 Based on these observations, it is conceivable that a corroding magnesium-organic environment interface could provide a niche where bacteria could initially settle and thrive as a first step toward biofilm formation. However, in vivo imaging and electron microscopic analysis in this study additionally demonstrated the spreading of the infection into peri-implant tissue pockets.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of dissolution and osmotic pressure decline over 2 days, however the pH shift may also have a negative effect on S. epidermidis growth over the 7-day period. The impact on the planktonic population may be less significant due to reduced exposure to these factors (13,29). …”
Section: Discussionmentioning
confidence: 99%
“…These findings were in line with reports of cytotoxic effects of magnesium in vitro against mammalian cells and bacteria that appeared to be mainly due to pH increases. 32,44,45 Whereas pH increases are the result of magnesium corrosion and magnesium hydroxide production it is conceivable that in comparison to pure crystalline magnesium hydroxide additional components such as proteins or phosphates in metallic magnesium implant corrosion layers could enhance the biocompatibility in vivo. 46,47 The findings do not entirely exclude the possibility that under particular conditions magnesium corrosion, excess Mg 21 ions or moderate pH increases could stimulate the differentiation of osteogenic cells.…”
Section: Discussionmentioning
confidence: 99%